2016
DOI: 10.1111/iere.12150
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Fiscal Balance in Japan*

Abstract: Japan is aging and has the highest government debt‐to‐output ratio among advanced economies. In this article, we build a micro data‐based, large‐scale overlapping generations model for Japan in which individuals differ in age, gender, employment type, income, and asset holdings, and incorporate the Japanese pension rules. Using existing pension law, current fiscal policy, and medium variants of demographic projections, we produce future paths for government expenditures and tax revenues, with implications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 19 publications
2
23
0
1
Order By: Relevance
“…Our paper is also connected to a large body of literature that quanti…es the …scal costs of population aging in advanced economies and studies the implications of pension and tax policy reforms designed for the mitigation of these …scal costs. Various reforms have been proposed to reduce the cost of the social security programs or raise revenue to fund them (e.g., see Kotliko¤ et al (2007), Krueger and Ludwig (2007), Kitao (2014), Nishiyama (2015) and McGrattan and Prescott (2017) for the US; Braun and Joines (2015), Kitao (2015) and Imrohoroglu et al (2016) for Japan; and Kudrna et al (2019) for Australia). McGrattan and Prescott (2017) in particular consider several reform proposals to switch from a pay-as-you-go (PAYG) social security system that relies on high payroll taxes to a fully-funded, saving-for-retirement system in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Our paper is also connected to a large body of literature that quanti…es the …scal costs of population aging in advanced economies and studies the implications of pension and tax policy reforms designed for the mitigation of these …scal costs. Various reforms have been proposed to reduce the cost of the social security programs or raise revenue to fund them (e.g., see Kotliko¤ et al (2007), Krueger and Ludwig (2007), Kitao (2014), Nishiyama (2015) and McGrattan and Prescott (2017) for the US; Braun and Joines (2015), Kitao (2015) and Imrohoroglu et al (2016) for Japan; and Kudrna et al (2019) for Australia). McGrattan and Prescott (2017) in particular consider several reform proposals to switch from a pay-as-you-go (PAYG) social security system that relies on high payroll taxes to a fully-funded, saving-for-retirement system in the US.…”
Section: Introductionmentioning
confidence: 99%
“…The government is assumed to have three fiscal measures to finance each of the two consolidation plans: (i) the income tax rates, (ii) the consumption tax rate and (iii) transfer payments. 17 The adjustments in income or consumption taxes or transfer payments are made to balance the government budget constraint in (6) from year 2015 onwards. While it is straightforward to implement the consumption tax adjustments via temporary increases in the effective consumption tax rate, τ c t , additional assumptions need to be made for the other two measures.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the change in labour supply must be matched by the change in the capital stock in the long run. The observed difference between the long run effects on labour and capital inTable 4is due to the changes in the effective tax rate on firm's profits (that are to match observed company tax revenues in % of GDP) during the calibration period of 2009-14, which alter the capital labour ratio in the long run 17. We also consider two alternative tax measures to repair the government budget: (i) temporary levy on labour income and (ii) temporary levy on total assets income.…”
mentioning
confidence: 98%
“…A large number of studies have estimated that the consumption tax (VAT) rate, which is currently at 8%, must be increased to the range of 20–60% in order to ensure sustainability of the government budget (e.g., Braun and Joines ; Hansen and İmrohoroğlu ; Hoshi and Ito ; Kitao ; Miyazawa and Yamada ). Other studies have indicated that measures like drastically cutting down social security benefits and increasing social security contributions, taken either independently or together, are inevitable (e.g., İmrohoroğlu, Kitao, and Yamada ; Kitao ).…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…measures like drastically cutting down social security benefits and increasing social security contributions, taken either independently or together, are inevitable (e.g.,İmrohoroglu, Kitao, and Yamada 2016;Kitao 2017).…”
Section: Institutional Backgroundmentioning
confidence: 99%